Penerapan Sistem Demokrasi dalam Keluarga Sebagai Langkah Awal Penyetaraan Gender - Muhammad Fadhly Akbar; Heriansyah (Al-Qadlaya : Jurnal Hukum Keluarga Islam, 2021)
Gender equality efforts have severe challenges. Therefore it is necessary to have a democratic system in a family as an offer of solutions in the framework of the beginning of gender equality. This study used a descriptive qualitative approach and the type of the method was field research. Data sources are several families with patrilineal, matrilineal and bilateral systems. Data collection using interview and participatory observation methods are unstructured. Data will be analyzed using Jean-Jaques Rousseau's democratic theory with John Rawls's theory of justice as a supporting theory. The results of this research are; (1) democratic system is a system that is able to found justice, freedom and equality in line with the steps of gender equality, because between democracy and gender equality have the same spirit; it’s justice, equality and freedom; (2) the role of mothers as madrastul ula is very big support in efforts to give a stimulus of justice, equality, and freedom for children in early age; (3) the implementation of the democratic system in the family can be the first step for gender equality efforts both within the family environment itself and in the other social environments. This can be showen from how the division of rights and obligations in the family that implements a democratic system that is not gender biased